A Real Test and Simulation Result Comparison of Selected Properties of Hybrid Composite Materials - Daneshjo, Naqib; Sabadka, Dusan; Malega, Peter (Engineering, Technology & Applied Science Research, 2024)
In this study, the notion of composite materials is thoroughly assessed. Actual and simulation in a specific computer software stress testing of hybrid composites are investigated. The paper deals with the mechanics of rigid bodies, their elasticity, strength, and stiffness. In addition to a general overview of the former’s behavior and properties, this paper presents the possibility of calculating the bearing capacity of various materials in relevant computer programs. The production and testing process of the composite samples are described. The latter are then subjected to simulated tests in computer software. The main objective of this study is to compare real test results of hybrid composites, namely combined carbon fibers, glass fibers, aramid-carbon fibers, aramid honeycomb, and metal mesh with the simulation findings.